Pott's Disease: An Emerging Source of Potentially Inappropriate Treatment - Esposito, Silvia; Moscatelli, Marco; Schiariti, Marco Paolo; Viganò, Ilaria; Pantaleoni, Chiara; Marucci, Gianluca (Neuropediatrics, 2019)
Spinal Tuberculosis in children is uncommon, even more so in cases of involvement of posterior vertebral elements, and its diagnosis is often delayed. Here we report the case of a young female presenting neuroradiological features and clinical symptoms suspicious for malignant tumor. Histological examination of biopsy specimen evidenced a Pott's disease. We highlight the importance of suspecting this disorder in children with both aspecific systemic and neurological symptoms, in order to reach a timely diagnosis for appropriate and targeted intervention, avoiding the risk of overtreatment and malpractice claims.
Keywords: Pott's disease; spinal tuberculosis; tuberculosis; children